Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.3109/00365528709011143
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Secretion in Pregnancy

Abstract: The gallbladder volume is increased in pregnancy, and its contraction during a meal is impaired. This is of importance for the increased risk of gallstones in pregnancy, since it may cause retention of cholesterol crystals in the gallbladder lumen. Cholecystokinin (CCK) is responsible for the food-induced gallbladder contraction. We have consequently measured the plasma concentrations of CCK in the fasting and the stimulated state in pregnant women and in age-matched non-pregnant controls. In a subset of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…CCK secreted from the duodenum during food intake induces satiety in addition to growth of the pancreas and gastrointestinal function (Geary 2001; Gutzwiller et al 2000). Basal CCK levels are increased or do not differ in pregnant women as compared with non-pregnant women (Frick et al 1990; Radberg et al 1987). However, it is also possible that isoforms of CCK do differ between pregnant and non-pregnant women.…”
Section: Part I: Pregnancy and Food Intake Regulationmentioning
confidence: 99%
“…CCK secreted from the duodenum during food intake induces satiety in addition to growth of the pancreas and gastrointestinal function (Geary 2001; Gutzwiller et al 2000). Basal CCK levels are increased or do not differ in pregnant women as compared with non-pregnant women (Frick et al 1990; Radberg et al 1987). However, it is also possible that isoforms of CCK do differ between pregnant and non-pregnant women.…”
Section: Part I: Pregnancy and Food Intake Regulationmentioning
confidence: 99%
“…In own experiments, we have found that the levels of cholecystokinin (CCK) rise in pregnant dogs (5). Recently an enhanced post-prandial rise of CCK levels was demonstrated in pregnant women (6). Since CCK stimulates pancreatic exocrine secretion, insulin release (7) and even the growth of the pancreas, enhanced levels contribute to an optimized digestive capacity and as a consequence to the weight gain observed during pregnancy.…”
mentioning
confidence: 99%
“…The peak/basal ratio was around 10 for both groups. This response to the test meal is larger than that to Emtobil (a formula con taining sorbitol and peanut oil), which was used in a recent study [14], In that study, it was found that pregnant women had a raised stimulated CCK secretion compared to con trols. The test meal used in the present study is more physiological in volume and compo sition than that used in the quoted study, and then there is no difference in CCK secre tion between pregnant women and con trols.…”
Section: Discussionmentioning
confidence: 89%
“…Ultrasound has been used in several studies to assess gastric emptying and motility [15][16][17] and has also been used to measure gallbladder contraction [14,18,19], In the present study, we have measured gastric and gallbladder volumes with ultra sound, and also CCK secretion, in women in the third trimester of pregnancy and in non pregnant controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation